UNSUR-UNSUR INTRINSIK CERPEN âLá¾¹ TA BAHÅª AL-FIRá¾¹KHâ DALAM ANTOLOGI CERPEN âULBATUN MIN A - AFÄªá¸¤ KARYA Iá¸¤Sá¾¹N âABDU AL-QUDDÅªS: ANALISIS STRUKTURAL ROBERT STANTON - , IBNUS SAKAN AL FAISHAL ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Story \"La T al-Fir kh\" in the anthology âUlbatun min as- á¿ is a short story that was written by I s n âA du l-Qudd s. This short story talks about the life of a egyptian who experienced monomania in his childhood. This monomania made him do the crime subconciously. He became a murder and hurt someone with a broad-bladed knife. This behavior is referred to as the psychological psychopathic diseases. He recovered at the age of 41 years and behave like a normal people. The purpose of this study is to investigate and dissect the elements intrinsic to the reference story \"La T al-Fir kh\" in the anthology âUlbatun min a - afá¿ This study use structural analysis with qualitative method. This short story tells us that the soul has experienced monomania by the main character. The Ideology carried by the main character is a crime that was not coming from sharp weapons but by human beings themselves.